Tinjauan Kesesuaian Fasilitas Kerja PT BMJ dari Sisi Ergonomi - Dimas Yoga Akhirul; Apid Hapid Maksum; Suhartono Suhartono (Peneliti.net, 2022)
In the development of technology that is growing over time. The principle of ergonomics is a guideline in applying ergonomics in the workplace. Anthropometry comes from the word anthropos which means human and metri which means size. In this data collection procedure the researcher carries out the stages carried out: Preparing the tools to be used, calibration of the tool (digital scales) whether it is still functioning properly or not and takes measurements. Based on the results obtained from data can be used to make the design of a work equipment, for example table and chair design for office standards. Each measurement result can be used to design a equipment design by taking an average value of an anthropometric measurement